Inclusion and Allyship in Orthopaedic Surgery Training and Practice - Feroe, Aliya G. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Over the last several years, there has been an increased focus on diversity, equity, and inclusion in undergraduate and graduate medical education. Creating a culture of inclusion is necessary to recruit and retain diverse healthcare workers and reap the benefits of a diverse workplace. Allyship serves to build such a culture of inclusion by supporting, amplifying, and promoting marginalized voices. The journey towards active allyship requires identifying personal privilege, power, and biases, seeking out education on the broad range of experiences and challenges faced by many individuals from marginalized groups, and empowering these individuals to lead and succeed. Ultimately, a culture of inclusion and allyship will help to optimize the medical training and practice environment for the benefit of patients, colleagues, and trainees alike.